2019
DOI: 10.1002/jcp.29401
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells for amyotrophic lateral sclerosis/motor neuron disease: A clinical and preclinical systematic review

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder characterized by neuronal degeneration and inflammation in the nerves. The role of the immune system has been concentrated by researchers in the etiopathogenesis of the disease. Given the inhibitory roles of regulatory T cells (Tregs), it is expected that increasing or activating their populations in patients with ALS can have significant therapeutic effects. Here we searched databases, including CENTRAL, MEDLINE, CINAHL Plus, http://clinicalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
0
17
0
7
Order By: Relevance
“…Disease progression is associated with conversion to a neurotoxic inflammatory response dominated by type 1 microglia (M1) and dysfunctional Tregs, which can no longer suppress Th1 and Th17 lymphocytes, as well as increased levels of pro‐inflammatory cytokines (IL‐1β, IL‐6, interferon [IFN]‐γ and tumour necrosis factor α) 11,12 . A correlation between Tregs and the rate of disease progression has been previously established in ALS and was associated with neuroprotective and neurodegenerative effects in ALS mouse models and some clinical trials, 16,18 although other clinical trials have not reported a clinic benefit despite an increase in percentage of Tregs 19 . Importantly, the loss of Tregs’ suppressive ability in patients with ALS was reported to be transient, and the ability was regained when they were expanded in a different environment 17,20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease progression is associated with conversion to a neurotoxic inflammatory response dominated by type 1 microglia (M1) and dysfunctional Tregs, which can no longer suppress Th1 and Th17 lymphocytes, as well as increased levels of pro‐inflammatory cytokines (IL‐1β, IL‐6, interferon [IFN]‐γ and tumour necrosis factor α) 11,12 . A correlation between Tregs and the rate of disease progression has been previously established in ALS and was associated with neuroprotective and neurodegenerative effects in ALS mouse models and some clinical trials, 16,18 although other clinical trials have not reported a clinic benefit despite an increase in percentage of Tregs 19 . Importantly, the loss of Tregs’ suppressive ability in patients with ALS was reported to be transient, and the ability was regained when they were expanded in a different environment 17,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Dimethyl fumarate, an FDA‐approved medication used for the treatment of relapsing‐remitting multiple sclerosis, 22,23 has been shown to alter immune response towards more anti‐inflammatory subsets. Specifically, dimethyl fumarate increased the number of anti‐inflammatory CCR3 + Th2 and Treg cells, shifting the pro‐ to anti‐inflammatory ratio (Th2/Th1Th17 and Treg/Th1Th17), with a simultaneous reduction in pro‐inflammatory T cells (CD4 + IFN‐γ; CD8 + IFN‐γ), thus highlighting its potential as a neuroprotective agent 17–19 . As such, the objective of this phase 2, randomised, placebo‐controlled, multicentric, double‐blind study was to assess the efficacy and safety of dimethyl fumarate in patients with ALS.…”
Section: Introductionmentioning
confidence: 99%
“…MDSCs limit immunological responses in a variety of ways, including by suppressing effector T cells and inducing Tregs (Nagaraj et al 2013;Rajabinejad et al 2020;Rajabinejad et al 2019;Kong et al 2013). Many factors work together as a complex network to ensure the expansion, activation, and survival of MDSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional restriction, hypoxia, abnormal organelles, exogenous toxins/chemicals, and oxidative stress are all known to promote autophagy. Autophagy may thus have a role in a variety of pathophysiological conditions, including malignancy (Barbosa et al, 2019; Rajabinejad et al, 2020). There are currently two theories about the function of autophagy in cancers.…”
Section: Introductionmentioning
confidence: 99%